1994
DOI: 10.1111/j.1464-5491.1994.tb00349.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in Secretion, Sensitivity, and Hepatic Extraction of Insulin in Black and White Americans

Abstract: Hyperinsulinaemia and abnormalities in hepatic insulin extraction commonly coexist in ethnic groups with severe insulin resistance. Therefore, we compared the effects of ethnicity on glucose/insulin/C-peptide dynamics, hepatic insulin extraction, and insulin sensitivity in healthy black (n = 32) and white (n = 30) Americans. Standard oral glucose tolerance test (OGTT) and tolbutamide-modified, frequently sampled, intravenous glucose tolerance (FSIVGT) tests were performed in each subject. Insulin sensitivity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
135
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(163 citation statements)
references
References 27 publications
25
135
1
Order By: Relevance
“…Similarly, insulin clearance was lower in African Americans for a given insulin sensitivity tertile. Our finding that insulin clearance is lower in African Americans than in subjects of White European origin, thus contributing to higher peripheral insulin concentrations, is in agreement with several other studies [28,29]. The finding of a similar pattern of EIR adaptation to increasing insulin resistance across ethnic groups is at odds with a previous study [30], which demonstrated failure of such compensation in obese African American young people.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, insulin clearance was lower in African Americans for a given insulin sensitivity tertile. Our finding that insulin clearance is lower in African Americans than in subjects of White European origin, thus contributing to higher peripheral insulin concentrations, is in agreement with several other studies [28,29]. The finding of a similar pattern of EIR adaptation to increasing insulin resistance across ethnic groups is at odds with a previous study [30], which demonstrated failure of such compensation in obese African American young people.…”
Section: Discussionsupporting
confidence: 90%
“…As proinsulin and insulin have different MCRs (35,36), the ratio of circulating proinsulin-to-insulin is controlled by the rates of secretion and clearance of both proinsulin and insulin. Furthermore, there is considerable intra-and inter-individual variation in the clearance of insulin, especially in hepatic insulin extraction, in many different physiological (37) and pathological conditions (38). Since C-peptide accurately reĀÆects the b cell secretory capacity (39) and, similarly to proinsulin, the hepatic extraction of C-peptide is negligible (40,41), the ratio of proinsulin-to-C-peptide may be considered as a better indicator of distressed b cells than is the ratio of proinsulin-to-insulin.…”
Section: Controlsmentioning
confidence: 99%
“…Nondiabetic black and MexicanAmerican subjects appear to have decreased insulin sensitivity when compared with white subjects (12). Previous studies have shown that there may be ethnic differences in secretion, sensitivity, and hepatic extraction of insulin in black and white Americans (13). Mexican-American subjects have higher insulin levels than white subjects, even after adjustment for BMI (14).…”
mentioning
confidence: 98%